Reliability of SPAD meter to indicate foliar nitrogen content in mature oil palm - Salim, Muhammad Zafrullah (2015)
Nitrogen (N) is important element in oil palm. It contributes to foliar development and served as a health parameter. N deficiency can affect productivity and yield of oil palm. On the other hand, excessive application can cause leaching and pollution of underground water. In seeking for an alternative to the conventional foliar analysis for N recommendation in oil palm management, SPAD meter is a handheld device that offers estimation of relative chlorophyll content in the leaf that could be directly related to N foliar content. It is non-destructive and affordable. This device proves to be convenient to estimate N content compare to the conventional methods such as soil and foliar sampling. The objective of this study is to determine the relationship between SPAD meter readings with the foliar N content in mature oil palm. This research was carried out in UMB Plantation in Machap Umboo, Melaka. The field Melaka Pinda planted in 2002 and Melaka Pinda 2005 were selected to conduct this experiment. For both fields, 9 plots with 16 palms in each plot were selected. The palms has been fertilized with different rates of N (Ammonium Chloride) that were N0 = 0kg AC, N1 = 1kg AC and N2 = 2kg AC. The parameters recorded were the SPAD readings and N content of the palm. For SPAD measurement, frond number 17 was the preferred one. The relationship between foliar N content and SPAD value of oil palm leaves were analyzed and the results showed that no significant relationship between both parameters. The linear regression between N content and SPAD value were also analyzed, with the highest R² value is 0.1595. It is concluded that SPAD-502 meter is not a reliable tool to estimate foliar N content via relative chlorophyll content in mature oil palm but serves as an alternative way to estimate N deficiency in mature oil palm.